Cardiac Output during Total Hip Replacement in Dogs - Gantke, S.; Matis, U.; Böttcher, P.; Erhardt, W. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
Trans-oesophageal pulsed-wave Doppler echocardiography was evaluated as a noninvasive method of determining cardiac output during total hip replacement in 10 dogs. Cardiac output was estimated by determining the crosssectional area of the aorta via caudal transverse echocardiography and the outflow velocity of the ascending aorta via cranial transverse Doppler echocardiography. Thermodilution was used as the reference method. In addition, cardiopulmonary changes, at the time of femoral prosthesis insertion, were determined. Comparison of 160 measurements yielded a correlation coefficient of 0.48. Linear regression analysis revealed the equation, cardiac outputDoppler echocardiography = 0.45 cardiac outputthermodilution + 3.3. In comparison to thermodilution, trans-oesophageal pulsedwave Doppler echocardiography overestimated cardiac output at flow rates less than 61/min and underestimated the cardiac output at flow rates greater than 61/min. There was a significant decrease in the partial pressure of carbon dioxide at end-expiration (PETCO2), the systolic arterial blood pressure (mmHg) and the invasive stroke volume (ml/beat/m2) and a significant increase in the pulmonary vascular resistance (dynes/sec/cm5) immediately after insertion of the femoral prosthesis.The purpose of this study was to evaluate the trans-oesophageal pulsed-wave Doppler echocardiography as a noninvasive method of determining cardiac output in dogs during total hip replacement. Thermodilution was used as the reference method. The correlation coefficient was r = 0.48. In conclusion, this study confirms that the trans-oesophageal Doppler echocardiography is not suitable for measuring the absolute CO-value. This ultrasound technique only allows an approximate estimation of the CO-trend.
Keywords: Anaesthesia; cardiac output; trans-oesophageal echocardiography; thermodilution; total hip replacement